Analisis Sentimen Masyarakat Indonesia Terhadap Kebijakan Program Tapera Menggunakan Brand24 - Dyah Ratna; Rohmad Abidin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This research analyzes the sentiment of the Indonesian public towards the Housing Savings Program (Tapera) policy using netnography methods and the Brand24 analysis tool. The research method employed is qualitative descriptive with a netnographic approach, examining data from various social media platforms, blogs, videos, forums, news sites, and websites. Data were collected from May 14 to June 13, 2024, and analyzed to identify positive, negative, and neutral sentiments towards the Tapera policy. The results of the study show the dominance of social media as the primary source of public opinion, followed by TikTok and videos. This analysis provides a comprehensive overview of the public's response to the Tapera policy, which can serve as a basis for decision-making and the formulation of more effective policy strategies.